Effect of Aging on Motor Inhibition during Action Preparation under Sensory Conflict - Duque, Julie; Petitjean, Charlotte; Swinnen, Stephan P. (Frontiers in Aging Neuroscience, 2016)
Motor behaviors often require refraining from selecting options that may be part of the repertoire of natural response tendencies but that are in conflict with ongoing goals. The presence of sensory conflict has a behavioral cost but the latter can be attenuated in contexts where conflict is expected in advance, producing a behavioral gain compared to contexts where conflict occurs in a less predictable way. In the present study, we investigated the corticospinal correlates of these behavioral effects (both conflict-driven cost and context-related gain). To do so, we measured motor-evoked potentials (MEPs) elicited by transcranial magnetic stimulation over the primary motor cortex of young and healthy older adults performing the Eriksen Flanker Task. Subjects performed button-presses according to a central arrow, flanked by irrelevant arrows pointing in the same (congruent trial) or opposite direction (incongruent trial). Conflict expectation was manipulated by changing the probability of congruent and incongruent trials in a given block. It was either high (mostly incongruent blocks, MIB, 80% incongruent trials) or low (mostly congruent blocks, MCB, 80% congruent). The MEP data indicate that the conflict-driven behavioral cost is associated with a strong increase in inappropriate motor activity regardless of the age of individuals, as revealed by larger MEPs in the non-responding muscle in incongruent than in congruent trials. However, this aberrant facilitation disappeared in both groups of subjects when conflict could be anticipated (i.e. in the MIBs) compared to when it occurred in a less predictably way (MCBs), probably allowing the behavioral gain observed in both the young and the older individuals. Hence, the ability to overcome and anticipate conflict was surprisingly preserved in the older adults. Nevertheless, some control processes are likely to evolve with age because the behavioral gain observed in the MIB context was associated with an attenuated suppression of MEPs at the time of the imperative signal (i.e. before conflict is actually detected) in older individuals, suggesting altered motor inhibition, compared to young individuals. In addition, the behavioral analysis suggests that young and older adults rely on different strategies to cope with conflict, including a change in speed-accuracy tradeoff.